Implementasi Manajemen Peserta Didik untuk Meningkatkan Mutu Pendidikan - Roudhotun Nadhifah (Universitas Negeri Malang, 2023)
Abstract: Student management bringing students from different backgrounds by prioritizing of mutual respect.Student management includes elements that support the best possible development of students during the educational process at school. In the management of students to improve the quality of education there are three steps in improving the quality of education including: improving the quality of input, facilities and infrastructure, and other academic activities. This article uses the library research method, also known as literature research. This research was conducted by collecting material from various references in books and journals to convey various theories. The aim of quality management is to improve performance both internally and externally in order to increase productivity, efficiency and quality of work and the main objective in improving quality of education is the quality of education. Implementation is an effort to reduce the gap between the practices implemented and the suggested practices in innovation. The process by which educational institutions are responsible for protecting the rights of citizens who are within the scope of these educational institutions, especially the rights of stakeholders such as teachers, students and parents of students, is reflected in the implementation of quality assurance.Keywords: implementations; students management; quality of educationAbstrak: Manajemen peserta didik menyatukan peserta didik dari latar belakang yang berbeda-beda dengan mengedepankan nilai saling menghargai. Manajemen peserta didik mencakup elemen yang mendukung perkembangan siswa dengan sebaik-baiknya selama proses pendidikan di sekolah. Dalam manajemen peserta didik untuk meningkatkan mutu pendidikan terdapat tiga langkahlangkah dalam meningkatkan mutu pendidikan meliputi: peningkatan mutu imput, sarana dan prasarana, serta kegiatan akademik yang lainnya. Artikel ini menggunakan metode penelitian pustaka atau disebut juga dengan penelitian literatur. Penelitian ini dilakukan dengan mengumpulkan bahan dari berbagai referensi di buku dan jurnal untuk menyampaikan berbagai teori. Tujuan manajemen mutu adalah untuk meningkatkan kinerja baik secara internal maupun eksternal guna meningkatkan produktivitas, efisiensi dan kualitas kerja serta tujuan utama dalam meningkatkan mutu pendidikan ialah kualitas pendidikan. Implementasi merupakan upaya untuk mengurangi kesenjangan antara praktik yang dilaksanakan dengan praktik yang disarankan dalam inovasi. Proses dimana lembaga pendidikan bertanggung jawab untuk melindungi hak-hak warga yang berada pada ruang lingkup lembaga pendidikan tersebut, terutama hak pemangku kepentingan seperti guru, siswa dan orang tua siswa, tercermin dalam pelaksanaan penjaminan mutu. Kata kunci: implementasi; manajemen peserta didik; mutu pendidikan